2019
DOI: 10.1080/21670811.2018.1556314
|View full text |Cite
|
Sign up to set email alerts
|

Fake News, Real Money: Ad Tech Platforms, Profit-Driven Hoaxes, and the Business of Journalism

Abstract: Following the viral spread of hoax political news in the lead-up to the 2016 U.S. presidential election, it's been reported that at least some of the individuals publishing these stories made substantial sums of money-tens of thousands of U.S. dollars-from their efforts. Whether or not such hoax stories are ultimately revealed to have had a persuasive impact on the electorate, they raise important normative questions about the underlying media infrastructures and industries-ad tech firms, programmatic advertis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 10 publications
0
71
1
4
Order By: Relevance
“…This includes factors such as time and location (Lian, Cha, and Xu 2019). It also includes the need for ongoing considerations about where brand messages are being placed (even if programmatically), as evident from discussions about advertising supporting mis-and disinformation websites (Mills, Pitt, andFerguson 2019, Braun andEklund 2019), or even recent boycotts or actions to dissociate one's brand from specific social media platforms or channels.…”
Section: Fostering Engagement With Interaction Planningmentioning
confidence: 99%
“…This includes factors such as time and location (Lian, Cha, and Xu 2019). It also includes the need for ongoing considerations about where brand messages are being placed (even if programmatically), as evident from discussions about advertising supporting mis-and disinformation websites (Mills, Pitt, andFerguson 2019, Braun andEklund 2019), or even recent boycotts or actions to dissociate one's brand from specific social media platforms or channels.…”
Section: Fostering Engagement With Interaction Planningmentioning
confidence: 99%
“…Some attempts to define what constitutes fake news have focused on academic discourse (Lee 2018;Tandoc Jr et al 2018) or on perceptions in industry after the 2016 election (Braun and Eklund 2019). Regarding the first, it was shown that from 2003 to 2017 the term "fake news" has been used to refer to things as varied as news satire, parody, fabrication, manipulation, advertising, and propaganda (Tandoc Jr et al 2018).…”
Section: Conceptual Mattersmentioning
confidence: 99%
“…Caught in the melee of advancing technologies and their implications for the hitherto industry of journalism, further challenges have emerged including, most recently, confrontations to our understanding of journalism as malevolent actors spread something other-than-news under the guise of journalism (Waisbord 2018, c.f. Tandoc, Ling, and, as audiences struggle to scrutinize and verify information as they too navigate change , and as advertisers seize on "fake news" as a revenue stream (Braun and Eklund 2019). The fact that content that disrupts journalism's allegiance with truth-telling succeeds creates incipient challenges as does the success of third-party digital platforms such as Facebook, where distribution and exposure are beyond the control of newsrooms, and fail to provide significant revenue streams for "real" news media (Myllylahti 2018).…”
Section: Revisiting the Burgeoning Line Of Research Into Digital Jourmentioning
confidence: 99%